PEMANFAATAN IPAD SEBAGAI PENGGANTI BUKU CETAK DALAM PEMBELAJARAN: STUDI KASUS DI SEKOLAH PHATNAWITYA YALA - Setiawan, Agung; Zuliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital technology has brought significant changes in the world of education, including in the use of learning media. One emerging innovation is the use of iPads as a substitute for printed textbooks in the learning process. This study aims to describe the implementation of iPad use in learning activities at Phatnawitya Yala School, analyze the abilities of teachers and students in utilizing these devices, and identify obstacles encountered in its implementation. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that the use of iPads can improve learning efficiency and access to digital learning resources, but still faces obstacles such as teacher readiness, supervision of device use, and limited digital literacy. Strategies are needed to mentor and strengthen teacher competencies so that the use of iPads can run optimally and in accordance with educational goals, especially from the perspective of Islamic Religious Education.